Pengaruh Penerapan E-Government terhadap Kinerja Pegawai pada Dinas Pemberdayaan Perempuan dan Perlindungan Anak Provinsi Sumatera Selatan - Rahmawati Rahmawati; Dwinur Febriana (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
The implementation of E-government has an important role in an organization. All things that include the implementation of e-government in an organization or government must be an important concern for the management of the organization, with the implementation of e-government that meets the standards according to the instructions of the President of the Republic of Indonesia Number 3 of 2003, it will improve employee performance, including through application applications. e-government. The availability of the application of E-government can improve employee performance and organizational work productivity. The method in this study uses quantitative methods. In collecting data, the author uses a questionnaire as a data collection tool. As well as using the determinant coefficient test and simple linear regression in data analysis techniques. This research was conducted at the Office of Women's Empowerment and Child Protection in South Sumatra Province with a total of 49 respondents. Based on the results of the study showed that all the results of the hypothesis in the study were proven significantly. This is indicated by the results of the t-count 3.768 > t-table 0.281. From the results of these studies, it can be concluded that there is a strong and positive influence between the implementation of e-government on employee performance at the Office of Women's Empowerment and Child Protection in South Sumatra Province.